2013
DOI: 10.3354/ame01611
|View full text |Cite
|
Sign up to set email alerts
|

Elemental quotas and physiology of a southwestern Pacific Ocean plankton community as a function of iron availability

Abstract: X-ray fluorescence maps of P, Fe and Zn in an autotrophic flagellate overlaid on an X-ray fluorescence spectrum for the cell. Scale bar = 2 µm. Data collected by: B. S. Twining KEY WORDS: Cellular iron quotas · Phytoplankton · Marine biogeochemistryResale or republication not permitted without written consent of the publisher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…The Chaetoceros-like diatoms had a~threefold variation in iron quotas with time and hence with changing dissolved iron concentrations and availability ( Figure 6). This latter range of iron quotas is of the same order as those reported for natural phytoplankton communities in response to purposeful iron enrichment in shipboard [Wilhelm et al, 2013] and mesoscale in situ [Twining et al, 2004] studies.…”
Section: Ecological Controls On Iron Quotas In the Ocean?supporting
confidence: 75%
“…The Chaetoceros-like diatoms had a~threefold variation in iron quotas with time and hence with changing dissolved iron concentrations and availability ( Figure 6). This latter range of iron quotas is of the same order as those reported for natural phytoplankton communities in response to purposeful iron enrichment in shipboard [Wilhelm et al, 2013] and mesoscale in situ [Twining et al, 2004] studies.…”
Section: Ecological Controls On Iron Quotas In the Ocean?supporting
confidence: 75%
“…By having a prolonged period of monitoring, it allowed to observe the full response from the diatom in all treatments, which would otherwise have been missed with a shorter timeframe. Such observation may aid in reconciling some of the contrasting results between studies that reported very low or negligible growth both in natural community and culture experiments (Wells et al, 1994;Eldridge et al, 2007;Hassler et al, 2011Hassler et al, , 2015Wilhelm et al, 2013).…”
Section: Skeletonema Costatum Response To Fedfb Boundmentioning
confidence: 63%
“…Gall, submitted) were constructed to collect particles and here are used to monitor the development of, and changes to, the marine‐snow‐associated bacterial community in situ . We describe the use of these traps to characterize changes in the particle‐associated microbial communities compared with free‐living bacterial communities in the water column during an initial diatom bloom and a secondary bloom codominated by cyanobacteria and diatoms, while the system transitioned from iron‐replete to iron‐limiting conditions (Wilhelm et al ., ).…”
Section: Introductionmentioning
confidence: 97%